Peer feedback and Chinese medical students’ English academic writing development: a longitudinal intervention study - Chenze Wu; Yao-Wu Zhang; Albert W. Li (BMC Medical Education, 2023)
Abstract Background Studies have documented that utilizing peer feedback can enhance students’ English academic writing skills. Little is known, however, about the effects of incorporating peer feedback to enhance English as a second language (L2) medical students’ academic writing performance. Methods This longitudinal interventional study examines Chinese medical students’ English academic writing skills development via peer feedback in four parallel classes over an 18-week semester between the experimental and control groups (n = 124). Results Significant increases in the experimental group’s performance in the post-test were found after 18-week instructions (pre- vs. post-test: overall score, p < .001; task response, p < .001; coherence and cohesion, p < .001; lexical resource, p < .001; grammatical range and accuracy, p < .001), and the effects were retained in the delayed post-test 6 weeks later (post- vs. delayed post-test: overall score, p = .561; task response, p = .585; coherence and cohesion, p = .533; lexical resource, p = .796; grammatical range and accuracy, p = .670). Little improvement was found in the control group in the post-test (pre- vs. post-test: overall score, p = .213; task response, p = .275; coherence and cohesion, p = .383; lexical resource, p = .367; grammatical range and accuracy, p = .180) or the delayed post-test (post- vs. delayed post-test: overall score, p = .835; task response, p = .742; coherence and cohesion, p = .901; lexical resource, p = .897; grammatical range and accuracy, p = .695). Between-group comparisons indicate that the experimental group outperformed the control group in the post- and the delayed post-tests, as shown in their overall score and scores on the four components. Conclusions Incorporating peer feedback into process-oriented medical English writing classroom teaching can effectively enhance Chinese medical students’ English academic writing skills over time, while the traditional product-oriented writing instructions had little help in improving Chinese medical students’ academic writing skills. This longitudinal intervention study develops our understanding of the effectiveness of peer feedback in L2 academic writing pedagogy. It offers instructional implications for L2 writing teachers to teach English academic writing among medical students in China and beyond. Limitations and suggestions for future studies are discussed.